Children in Digital Age – Hungarian Perspective - Halász, Csenge (Children in Digital Age, 2025)
Abstract:This chapter explores the legal framework for protecting children’s rights in Hungary, with particular emphasis on the challenges posed by internet and social media use. It begins by outlining the Hungarian legal definitions of childhood and minority, demonstrating how these relate to capacity, education, and criminal responsibility. The analysis highlights the growing presence of children on digital platforms and examines the potential threats to their fundamental rights, including privacy, freedom of expression, and protection from harmful content. Particular attention is paid to inconsistencies between international platform policies (e.g., Facebook’s age requirements) and Hungarian civil law. The chapter also investigates the phenomenon of “sharenting” and its impact on children’s privacy and identity development. It addresses legal gaps regarding parental overexposure of children online and the lack of sector-specific regulation. Case law in this field remains limited, but empirical studies indicate widespread online harm among minors. Institutional mechanisms - such as the National Media and Infocommunications Authority and NGOs like the Hintalovon Foundation - play an active role in education and prevention. In conclusion, while Hungary’s legal system provides a comprehensive basis for child protection, the rapid evolution of digital environments necessitates further regulatory adaptation and awareness-raising initiatives.Keywords: personality rights, children’s rights, social media, right to privacy, fundamental rights